EVALUASI DINAMIS KEMISKINAN IKLIM-RENTAN: INTERAKSI ANTARA SHOCK CUACA EKSTREAM DAN KEBERLANJUTAN ENERGI DI KOMUNITAS PEREMPUAN PEDESAAN - Aulia, Firli; BIllah, Zhelin Tri Sah; Rahmi, Nabilla Wasila (Visi Pencerah Nusantara, 2024)
Abstract This study aims to dynamically evaluate the relationship between extreme weather shocks and energy sustainability in shaping climate-vulnerable poverty among rural women communities. Although studies on climate poverty, gender inequality, and energy access have developed, the literature is still lacking in systematically integrating the three. This study employs a qualitative method using a Systematic Literature Review (SLR) approach on scientific publications over the past six years (2020–2025) obtained from the Dimensions and Scopus databases. Inclusion criteria were established to ensure the relevance and quality of the reviewed literature. The synthesis results indicate that rural women's resilience to climate impacts is significantly influenced by structural limitations, including social exclusion, unequal access to energy, and weak institutional capacity. Access to clean energy is a key determinant in strengthening socio-ecological adaptation, but its unequal distribution creates a complex ecosystem of vulnerability. This study recommends the need to develop gender-sensitive and community-based renewable energy intervention models. The main contribution of this research lies in the integration of three dimensions of vulnerability into a single evaluative framework, which is expected to enrich academic discourse and support inclusive policies based on climate justice.